Sending money home: a mixed-Methods study of remittances by migrant nurses in Ireland - McGee Hannah; Brugha Ruairí; Humphries Niamh (BMC, 2009)
Abstract Background This paper presents data on the remittances sent by migrant nurses to their families "back home". It gives voice to the experiences of migrant nurses and illustrates the financial obligations they maintain while working overseas. Although the international economic recession has decreased global remittance flows, they remain resilient. Drawing on the experiences of migrant nurses in Ireland, this paper indicates how and why migrants strive to maintain remittance flows, even in an economic downturn. Methods A mixed-methods approach was employed, and the paper draws on data from qualitative in-depth interviews undertaken with 21 migrant nurses in addition to a quantitative survey of 336 migrant nurses in Ireland. Results The survey of migrant nurses revealed that 87% (293) of the sample sent remittances on a regular basis. According to respondents, remittances made a huge difference in the lives of their family members back home. Remittances were used to ensure that family members could obtain access to health and education services. They were also used to provide an income source for family members who were unemployed or retired. As remittances played an essential role in supporting family members back home, respondent migrant nurses were reluctant to reduce the level of their remittances, despite the onset of a global recession. Respondents noted that an increased demand for remittances from their families coincided with a reduction in their own net salaries - as a result of increased taxes and reduced availability of overtime - and this was a cause for concern for Ireland's migrant nurses. Conclusion This paper provides insights into the importance of remittances in funding social support for family members in home countries. It also illustrates the sacrifices made by migrant nurses to ensure continuation of the remittances, particularly in the context of an economic recession.